A framework for understanding quality of life domains in individuals with the CDKL5 deficiency disorder. Issue 2 (18th December 2018) - Tangarorang, Jodilee; Leonard, Helen; Epstein, Amy; Downs, Jenny
Abstract : The CDKL5 deficiency disorder (CDD) is a rare condition caused by spontaneous mutations on the cyclin‐dependent kinase‐like 5 (CDKL5) gene. It is a severe and complex disability that markedly affects the individual's health and wellbeing. This study aimed to identify the quality of life (QOL) domains important for individuals with CDD. Twenty‐five parents of individuals registered in the International CDKL5 Disorder Database participated in semi‐structured telephone interviews to explore areas that supported or challenged their child's QOL. Rett syndrome (RTT) is another severe genetically‐caused neurodevelopmental disorder but is generally less severe than CDD. Qualitative data were analysed using directed content analysis, based on previously identified QOL domains for RTT that related to health and wellbeing, daily activities and community immersion and services. Each of the domains identified for RTT was represented in the CDD dataset overall and when the dataset was divided into three age groups: 3–5 years old; 6–18 years old; and older than 18 years. This is the first study to conceptualise factors important for individuals with CDD. Findings from this study will guide health professionals and other service providers who support individuals with CDD and will offer insight into choosing appropriate QOL instruments when measuring outcomes for this group.